Dynamics of the bacterial and archaeal communities in the Northern South China Sea revealed by 454 pyrosequencing of the 16S rRNA gene. (July 2015) - Xia, Xiaomin; Guo, Wang; Liu, Hongbin
Abstract: Dynamics of the prokaryote (bacteria and archaea) abundance and community compositions in the Northern South China Sea (NSCS) in August 2009 and January 2010 were studied by flow cytometric analysis and 454 pyrosequencing of the 16S RNA gene. Prokaryotic community structures in the NSCS varied across space and over time, and this variation was strongly correlated with NO 3 - concentration. Prokaryote in estuarine and coastal waters was more abundant, but relatively less seasonally dynamic than in the open ocean. Major bacterial and archaeal lineages showed different niche preferences. Archaeal community was dominated by Marine Group I and Marine Group II. Clusters of Marine Group I varied spatially, while clusters of Marine Group II varied seasonally. Synechococcus and Prochlorococcus were two major autotrophic bacteria found in the NSCS. Synechococcus prevailed at the estuarine station in summer, while Prochlorococcus had high abundance at open-ocean stations in summer. Subcluster 5.2 Synechococcus and Sub 5.1 clade II Synechococcus were the dominant Synechococcus lineages in the NSCS, with the former dominating in the estuary during summer and the latter dominating at all other stations. Our results suggest that prokaryotic assemblages are highly complex in the NSCS and are controlled by seasonal monsoon and river discharge, showing spatiotemporal variations.